Clinicopathological analysis of recurrent basal cell carcinoma of the eyelid - Iljin, Aleksandra; Zieliński, Tomasz; Antoszewski, Bogusław; Sporny, Stanisław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction: Basal cell carcinoma (BCC) is the most common malignant neoplasm of the eyelids and surrounding structures, usually developing in the area of the lower lid and medial canthus. Invasive forms of BCC are connected with a high risk of recurrence, often due to incomplete excision of these lesions. Aim: Clinical and pathological analysis of recurrent BCCs of the eyelids and surrounding structures. Material and methods : We present clinical and pathological analysis including immunohistochemical reaction to Ki-67 antigen of 19 patients (11 women, 8 men) operated for recurrent BCCs of the eyelids in 2000–2012. Results : In most cases, recurrences were present on the lower lid and in the medial canthus. In 15 patients the histopathological type did not change and in 4 cases it transformed into more invasive forms. The values of Ki-67 index for primary BCCs ranged between 1% and 20%, and for relapsing lesions between 11% and 48%. Conclusions : Proper clinical and pathological evaluation to determine the risk of relapse in BCCs of the eyelids and surrounding structures should include the analysis of prognostic factors, in particular location and size, histopathological type and radicalness of surgical treatment of primary BCCs. Clinical and pathological analysis of patients with recurrent BCC of the eyelids and surrounding structures should be combined with the evaluation of proliferation index Ki-67, which is essential for prognosis and choice of the appropriate therapeutic method.